Surface treatment by electric discharge machining of Ti-6Al-4V alloy for potential application in orthopaedics - Harcuba, Petr; Bačáková, Lucie; Stráský, Josef; Bačáková, Markéta; Novotná, Katarína; Janeček, Miloš (Journal of the mechanical behavior of biomedical materials, 2012)
This study investigated the properties of Ti-6Al-4V alloy after surface treatment by the electric discharge machining (EDM) process. The EDM process with high peak currents proved to induce surface macro-roughness and to cause chemical changes to the surface. Evaluations were made of the mechanical properties by means of tensile tests, and of surface roughness for different peak currents of the EDM process. The EDM process with peak current of 29 A was found to induce sufficient surface roughness, and to have a low adverse effect on tensile properties. The chemical changes were studied by scanning electron microscopy equipped with an energy dispersive X-ray analyser (EDX). The surface of the benchmark samples was obtained by plasma-spraying a titanium dioxide coating. An investigation of the biocompatibility of the surface-treated Ti-6Al-4V samples in cultures of human osteoblast-like MG 63 cells revealed that the samples modified by EDM provided better substrates for the adhesion, growth and viability of MG 63 cells than the TiO2 coated surface. Thus, EDM treatment can be considered as a promising surface modification to orthopaedic implants, in which good integration with the surrounding bone tissue is required.
Keywords: Prostheses and Implants; biokompatibilní potahované materiály; testování materiálů; Coated Materials, Biocompatible; protézy a implantáty; Biocompatible Materials; Bone and Bones; slitiny; biokompatibilní materiály; Humans; povrchové vlastnosti; Titanium; kosti a kostní tkáň; lidé; Alloys; Surface Properties; titan; Materials Testing